Sinusoid based calibration for holdup measurement in two-phase flow using helical capacitance sensor - Lim, L.G. (Institute of Electrical and Electronics Engineers Inc., 2017)
A helical capacitance sensor was designed to measure the holdup of two-phase stratified flow in horizontal pipe. The structure of 360° twisted helical capacitance sensor had been designed, analyzed and optimized using finite element method. A sinusoidal function was observed as the relationship between the capacitance readings and holdup. As the nonhomogeneity in the distribution of capacitance sensitivity field cannot be completely eliminated, a helical capacitance sensor was designed in such a way that a sinusoidal relationship was generated. The numerical readings and the approximation model obtained a very close agreement, where the mean absolute difference was about ±1. Besides, the effects of geometric parameters on the capacitance values were analyzed and investigated, where it was found that the symmetry of sinusoidal function can be modeled by adjusting the pitch of helix. © 2016 IEEE.